2015
DOI: 10.5811/westjem.2014.12.23706
|View full text |Cite
|
Sign up to set email alerts
|

Educational Technology Improves ECG Interpretation of Acute Myocardial Infarction among Medical Students and Emergency Medicine Residents

Abstract: IntroductionAsynchronous online training has become an increasingly popular educational format in the new era of technology-based professional development. We sought to evaluate the impact of an online asynchronous training module on the ability of medical students and emergency medicine (EM) residents to detect electrocardiogram (ECG) abnormalities of an acute myocardial infarction (AMI).MethodsWe developed an online ECG training and testing module on AMI, with emphasis on recognizing ST elevation myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 18 publications
(23 reference statements)
0
42
0
Order By: Relevance
“…[20][21][22][23] Online or web-based teaching has been shown to have comparable efficacy with more traditional lecture or workshop-based teaching in regard to ECGs. [24][25][26] It has been postulated that web-based training may, in fact, be more effective than traditional teaching methods. 27,28 Medical students appreciated a web-based program and attributed its success to greater immediacy, improved visualization, and interactivity.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Online or web-based teaching has been shown to have comparable efficacy with more traditional lecture or workshop-based teaching in regard to ECGs. [24][25][26] It has been postulated that web-based training may, in fact, be more effective than traditional teaching methods. 27,28 Medical students appreciated a web-based program and attributed its success to greater immediacy, improved visualization, and interactivity.…”
Section: Discussionmentioning
confidence: 99%
“…It remains important to review whether these novel teaching and learning methods are effective 26. Previous studies have shown that students’ knowledge of, and skills in the analysis and interpretation of ECGs improve with computer-assisted instruction (CAI) 27–34. However, these studies did not compare CAI to other methods of instruction and thus it cannot be concluded that CAI is better than traditional methods of ECG teaching.…”
Section: Introductionmentioning
confidence: 99%
“…The EM literature provides little guidance with regard to the optimization of ECG interpretation curricula. [8][9][10][11] In our training program residents are exposed to ECG interpretation teaching via didactic lectures, asynchronous learning modules, one-on-one dedicated training, and textbook review. Trainees also take the annual American Board of Emergency Medicine In-Training Examination, which includes ECG interpretation and questions related to cardiac emergencies.…”
Section: Discussionmentioning
confidence: 99%